TRADISI YANG TERLUPAKAN DALAM PERADABAN ISLAM - Pane, Ismail (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
Islamic civilization has a rich history with various traditions and practices that have contributed significantly to scientific, cultural, and religious developments. However, with the passage of time and social changes, many traditions have been forgotten or given little attention in modern society. This article examines several traditions that have simply been lost, from classical science and wisdom to art, manners and ethics in Islam. This research aims to explore Islamic traditions, describe their values ​​in the current context, and remind them of the importance of preserving them for future generations. The method used in this research is the SLR (Systematic Literature Review) method. The results and conclusions are that Islamic traditions are faced by the influence of globalization, modernization, as well as a lack of interest or understanding among the younger generation. By understanding, respecting and maintaining Islamic traditions, Muslims can maintain the cultural and spiritual riches that have been passed down from time to time.